Connective Learning as Teachers' Approach to One's Own Professional Development: The Case of Poland - Jolanta Karbowniczek; Dorota Zdybel (Ignatianum University Press, 2022)
Although the genesis of connectivism as a theory of learning in the digital age dates back to the early 2000s, in Polish pedagogy this concept remains relatively unknown, sparse in academic debates, and downright rare in empirical research. The main purpose of the article is to present the knowledge and opinions of Polish teachers regarding connectivism. To what extent do Polish teachers know the theory of connective learning? Which of its assumptions do they see as key? To what extent are they willing to apply these assumptions in practice as a path or tool for developing their own professional competences? These research questions were the basis for a survey, the presentation of which constitutes the backbone of this article. The research indicates a clear cognitive dissonance in the minds of the teachers surveyed: the gap between the perception of the potential values of connectivism and the ability/readiness to use its tools in their own learning. The summary of the text contains conclusions for in-service teacher training, which needs to be reorganized to include the most valuable connected learning instruments so as to provide teachers with the skills necessary for successful self-regulated learning in the digital age.